Comparative effectiveness and safety of direct oral anticoagulants compared to warfarin in morbidly obese patients with acute venous thromboembolism: systematic review and a meta-analysis - Mohamed Nabil Elshafei (9960500) (2020)
Direct oral anticoagulant (DOAC) agents are becoming the anticoagulation strategy of choice. However, their use in the treatment of acute venous thromboembolism (VTE) in morbidly obese patients (bodyweight of > 120 kg or BMI> 40 kg/m2) guarded. This is due to the scarce data supporting their use in this population. As a result, the International Society on Thrombosis and Haemostasis recommended against their use in this cohort of patients. New data emerged supporting the use of DOACs in these patients. Hence, we aimed to systematically review the literature exploring the efficacy and safety of these agents compared to warfarin in VTE treatment in morbidly obese patients. A systematic review of PubMed and EMBASE since inception until 01/04/2020. Subsequently, a non-inferiority (NI of 1.75) meta-analysis utilizing the random-effects model. Five observational studies (6585 patients) were included in our meta-analysis. DOAC analogs were non-inferior compared to warfarin in reducing the primary efficacy outcome of VTE recurrence (OR 1.07, 95% CI 0.93–1.23) and the primary safety outcome (major bleeding events) (OR 0.80, 95% CI 0.54–1.17). Our meta-analysis comprising real-world observational data concludes that the use of DOAC analogs in morbidly obese patients (bodyweight of > 120 kg or BMI > 40 kg/m2) is non-inferior with regards to efficacy and safety compared to warfarin. This finding helps to resolve the uncertainty associated with the use of DOACs in this cohort. Additionally, it invites for a confirmatory non-inferiority randomized controlled trial testing DOAC vs. Warfarin in this group of patients. Other Information Published in: Journal of Thrombosis and Thrombolysis License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s11239-020-02179-4